Analysis of The Secondary Metabolite of Kersen Leaf Extracts (Muntingia calabura L.) and Its Potential as Anti-Bacteria to Inhibit Aeromonas hydrophila - Gede Angga Krishna Fariestha; Sri Andayani; Uun Yanuhar (Research Journal of Life Science, 2018)
Aeromonas hydrophila is a gram-negative bacterium that massively attack aquatic organisms in fresh water, briny water and sea waters. Infection due to this bacterium caused septicemia in the host's body to the point of damaging the body's organs. Hence, alternative material is required in order to cope with this bacterium, which was by using natural material such as kersen leaf (Muntingia calabura L). The purpose of the research is to determine the effect of secondary metabolite contained in kersen leaf as anti-bacterial against Aeromonas hydrophila. This research used a method of MIC (Minimum Inhibitory Concentration) as an anti-bacterial test. In order to examine the secondary metabolite content, phytochemical screening and FTIR (Fourier Transform Infrared Spectroscopy) methods were used. The results obtained through the MIC test of 125 ppm is the minimum concentration capable of inhibiting the growth of Aeromonas hydrophila. Kersen leaf extracts is bacteriostatic anti-bacteria which only inhibit bacterial growth up to 24 hours. Phytochemical screening reported that kersen leaf extracts were positive of flavonoids, tannins, saponins, alkaloids and triterpenoids. Through FTIR test, it is known that phenol compounds were contained in kersen leaf extracts. This phenol is one of the metabolites with the function of anti-bacterial on this study.